Use of kinematical determinant to locate the centre of cyclones and the ring of maximum wind enclosing the centre (MAUSAM, 1978)
It is established that the kinematical determinant [k. {(Vu) x (Vv) }] can be used to determine the centre, of cyclones and the ring of maximum wind enclosing the centre.